COVID-19 vaccination coverage is extremely low among older population in Bangladesh: findings from a cross-sectional study. Issue 1 (31st January 2022) - Mistry, Sabuj Kanti; Ali, ARM Mehrab; Yadav, Uday Narayan; Huda, Md. Nazmul; Parray, Ateeb Ahmad; Mahumud, Rashidul Alam; Mitra, Dipak
ABSTRACT: This cross-sectional study was conducted in September 2021 among 1, 045 Bangladeshi older adults aged 60 years or above to explore the COVID-19 vaccination coverage and its associated factors. We used a semi-structured questionnaire to collect data on participants' sociodemographic and lifestyle characteristics, and COVID-19 related information (selected based on an extensive literature review). A multinomial logistic regression model was used to identify the factors independently associated with vaccine receipt. Nearly, two-thirds of the participants (64.5%) were unvaccinated and 12.5% received a single dose. Among the unvaccinated, approximately 94% reported that there was a problem in accessing the vaccine. We found that participants with formal schooling had 42% lower risk of being unvaccinated (RRR (Relative Risk Ratio) = 0.58, 95% CI 0.42–0.80) or 39% lower risk of receiving a single dose (RRR = 0.61, 95% CI 0.39–0.96) than the participants having no formal schooling. The middle family monthly income groups had 65% higher risk (RRR = 1.65, 95% CI 1.17–2.32) and rural participants had 84% higher risk (RRR = 1.84, 95% CI 1.26–2.70) of not receiving vaccines compared to their counterparts. Also, the participants with non-communicable chronic conditions had a significantly lower risk of being unvaccinated (RRR = 0.49, 95% CI 0.35–0.68) or receiving a single dose (RRR = 0.49, 95% CI 0.31–0.77) compared to their counterparts. This finding may help strengthen the existing efforts to maximize vaccine coverage among older populations in Bangladesh and reach herd immunity to break the transmission chain and gain greater overall population protection more rapidly.